FISH comets show that the salvage enzyme TK1 contributes to gene-specific DNA repair - McAllister, Katherine A.; Yasseen, Akeel A.; McKerr, George; Downes, C. S.; McKelvey-Martin, Valerie J. (Frontiers in Genetics, 2014)
Thymidine kinase 1 (TK1) is a salvage enzyme that phosphorylates thymidine, imported from surrounding fluids, to create dTMP, which is further phosphorylated to the DNA precursor dTTP. TK1 deficiency has for a long time been known to cause increased cellular sensitivity to DNA damage. We have examined preferential strand break repair of DNA domains in TK1+ and TK1- clones of the Raji cell line, by the Comet-FISH technique, in bulk DNA and in the actively transcribed tumour suppressor (TP53) and human telomerase reverse transcriptase (hTERT) gene regions, over 1 hour after 5Gy γ-irradiation. Results showed that repair of the TP53 and hTERT gene regions was more efficient in TK1+ compared to TK1- cells, while levels of genomic DNA repair were consistant between the two cell-lines. The targeted gene-specific repair in TK+ cells occurred rapidly, mainly over the first 15 minute repair-period. Therefore, TK1 is needed for preferential repair of actively transcribed regions, through a previously unsuspected mechanism. In principle, TK1 could exert its protective effects through supply of a supplementary dTTP pool for accurate repair of damaged genes; but Raji TK1+ cells in thymidine free media still show preferential repair of transcribed regions. TK1 therefore does not exert its protective effects through dTTP pools, but through another unidentified mechanism, which affects sensitivity to and mutagenicity by DNA damaging agents.